Physical fitness characteristics and performance in single-handed dinghy and 470 classes sailors - Pan, D.; Zhong, B.; Guo, W.; Xu, Y. (Journal of Exercise Science & Fitness, 2022)
Background/Objectives: The purpose of this study was to investigate the differences in the physical fitness characteristics of Chinese single-handed dinghy and 470 sailors, predict the single-handed dinghy sailors` physical factors on the performance by equation to guide the training. Methods: The sample of this study consisted of one hundred and sixty-seven Chinese sailors who participated in the 2020 China National Sailing Championships, K Independent Samples Test was used to analyze the differences of different classes sailors, and the performance of Laser and Laser Radial sailors were analyzed by step multivariate linear regression. Results: The results showed that the 470 helmsmen are shorter, lighter and have a lower BMI, 470 crew are similar in height to the single-handed dinghy sailors, but lower in weight and BMI. Laser sailors have better strength and flexibility than the ones of male 470. There is no significant difference in the physical fitness characteristics between the Laser Radial sailors and the female 470 crew, they both had better upper and lower body strength than female 470 helmsmen. The regression equation is possible to explain 65.5% of the performance of the sailors in Laser=90.963-1.33×sailing experience-0.461×bench press-0.018×cycling peak power out; The regression equation is possible to explain 76.7% of the performance of the sailors in Laser Radial=27.433-0.391×sailing experience+0.351×vertical jump-0.329×pull-up-0.027×cycling peak power out. Conclusions: Performance in laser and Laser Radial sailors will be determined by the technique and tactics (sailing experience) as well as physical fitness.